Abundance and ecology of Myctophidae fishes in the Gulf of Alaska in winter season - V. I. Radchenko; A. N. Kanzeparova; A. A. Somov; I. V. Grigorov (Известия ТИНРО, 2021)
Distribution and abundance of myctophid fish species in the upper epipelagic layer are analyzed based on results of surveys in the Gulf of Alaska in winters of 2019 and 2020. A common myctophid community driven by blue lanternfish Tarletonbeania crenularis was revealed that occupied likely the entire eastern part of the Subarctic Front zone eastward from 150ºW. Abundance and biomass of four mass myctophid species were generally comparable between the northeastern and northwestern Pacific. Small-sized juveniles prevailed among northern lampfish Stenobrachius leucopsarus, which were likely transported by the Subarctic Current and could be recruited to the Bering Sea stock. Patterns of daily vertical migrations are discussed for the mass myctophid species. New observations confirm general understandings on the myctophid species input to functioning of fish community.